Foreign direct investments in large-scale agriculture: the policy environment and its implications in Ethiopia - Persson, Atkeyelsh G M (School of Architecture, Planning and Geomatics, 2017)
In most African states, arable land and other natural resources play a pivotal role for economic growth and development. Ethiopia is one of those countries where agriculture is the backbone of the economy. Since the time of Emperor Haile Selassie I, Ethiopia has been attempting to advance the transformation of its agricultural sector by moving away from small-scale subsistence farming to large-scale commercial farming. It thus encouraged Foreign Direct Investment (FDI) in largescale agriculture. However, the military government that took power in 1974 reversed this. The current government of Ethiopia seized power from the military regime in 1991. Today the government once again advocates FDI in large-scale agriculture. This has led to an influx of foreign investors, especially in Gambella and Benshanguel-Gumuz Regional States. Various scholars, however, criticize the manner in which these investments have been taking place, arguing that the investments are neither pro-poor nor sustainable. Against this backdrop this research seeks to examine current policies, the patterns of investment they promote, and how these affect land-based resources and the wellbeing of communities. The study intends to provide information that may help improve the performance of FDI in terms of their sensitivity to poverty alleviation and sustainability. It also aims to boost current knowledge on FDI in agriculture in Ethiopia. The study was conducted using multiple data collection methods, including documentation, interviews, focus group discussions with the affected communities and direct observations in the case study areas. The results are analysed using pro-poor and sustainability frameworks for FDI in large-scale agriculture, along with findings of empirical studies on national FDI policies and practices in various parts of the globe. The analyses reveal that the Ethiopian investment policy's support to FDI in large-scale agriculture is inadequate. It focuses on giving incentives to attract FDI rather than ensuring the availability of quality institutions and sufficient infrastructure, which are vital for facilitating the operation and productivity of FDIs. Furthermore, the absence of community participation in the decision-making process for the agricultural investment projects in the case study areas portends significant negative implications for the wellbeing of local communities and the sustainability of the natural environment. The study recommends further research to investigate the economic viability of alternative land-based investments, such as eco-tourism, which is shown to be environmentally sustainable and can be shaped to be pro-poor. Also recommended is additional research into good practices for large-scale agricultural investments, that can be adapted to Ethiopian conditions, should the government opt to continue promoting FDI.